Reversible Verbal Memory Integration Deficits in Obstructive Sleep Apnoea. Issue 1 (25th March 2021) - Benkirane, Oumaïma; Neu, Daniel; Schmitz, Rémy; Dehon, Hedwige; Mairesse, Olivier; Peigneux, Philippe
When presented with novel but semantically related elements after learning verbal material, healthy participants tend to endorse these items as previously learned. This reflects the normal integration and association of novel verbal information into long-term memory. How obstructive sleep apnoea (OSA) negatively impacts verbal memory performance, and whether deficits are reversible following positive airway pressure (PAP) treatment, remain elusive. We investigated immediate and delayed OSA- and PAP treatment-related effects on verbal memory integration, using a false memory paradigm. Twenty-three patients with OSA learned lists of words semantically related to target non-presented words (1) at baseline after a polysomnography diagnosis night, (2) after a consecutive polysomnography night under PAP titration, and (3) after three months of compliant PAP treatment. At each session, participants learned 10 different lists of words, each list comprising 15 semantically related items. They had then to recognize 15 minutes later (after an intermediate vigilance task) previously learned words within a list including studied words (learned), unstudied but semantically related items (lures), and non-related unstudied items (controls). Sleep quality and fatigue questionnaires, and psychomotor vigilance tests (PVT) were administered at each session. PAP treatment led to OSA remission and improvement in objective and subjective sleep quality. Crucially, recognition of learned and lure words increased after the first night under treatment and remained stable three months later, suggesting successful memory integration and restoration of semantic processes. No treatment-related outcome was found on PVT performance. OSA exerts a detrimental but PAP-reversible effect on verbal learning and semantic memory integration mechanisms underlying the acquisition of novel memory representations.